POWER AND MANIPULATION DEPICTED BY MILES BRON IN GLASS ONION (2022) - Inkarizki Swedianisa Amalia; Slamet Setiawan; Syafi’ul Anam (Universitas Bunda Mulia, 2023)
This study is aimed to uncover the types of power and investigate how far power can lead to manipulate others in a movie entitled Glass Onion (2022), written and directed by Rian Johnson. The director portrays Miles Bron's exercise of power as if he had invited his friends to play a murder mystery game on his private island in Greece, yet Blanc solves it promptly. Miles is giving his friends a genuine opportunity to kill him since he is disgruntled; in fact, Duke died of a poisoned drink in moments. Due to the disruption caused by Miles' murder mystery game, this study focuses on studying the power wielded by the main character, Miles Bron. The researchers employed qualitative approach by using content analysis method to analyze the movie. Therefore, the data will be displayed in the form of word, phrase, sentence, and utterance produced by all movie’s characters. The findings suggest that Miles has used four types of power bases to control his friends; reward power, coercive power, referent power, and legitimate power. Furthermore, Miles was able to control his friends by disrupting their psychological awareness in chaotic situations such as the disappearance of Duke's gun and cellphone to manipulate the situation as well as the reason of Duke’s death.